Management of Respiratory Emergencies and Acute Respiratory Distress Syndrome (ARDS) in Emerging Infectious Diseases: A Literature Review on COVID-19 - Dhevi, Ni Made Saithanya Gitanjali; Setiasari, Febi Jian; Asriantin, Isna; Nitzana, Lale Nubya; Aghni, Hasna Tazkia (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Emerging infectious diseases, including SARS-CoV-2, have become major global health challenges with significant clinical and social impacts. One of the most frequent and fatal complications of COVID-19 is Acute Respiratory Distress Syndrome (ARDS), characterized by impaired gas exchange due to diffuse lung injury. This study is a narrative review analyzing 28 articles on the epidemiology, pathophysiology, clinical features, and management of COVID-19 related ARDS (CARDS). The findings show that CARDS presents with greater severity and higher mortality than ARDS caused by other etiologies, driven by excessive inflammatory responses, endothelial dysfunction, and microthrombosis. Clinical manifestations progress from early COVID-19 symptoms to worsening hypoxemia in accordance with the Berlin criteria. Emergency management of COVID-19 with ARDS emphasizes the ABCDE approach, stabilization of respiratory and circulatory functions, and indication-based interventions to prevent respiratory failure and improve oxygenation. This review is expected to serve as a comprehensive reference for healthcare professionals in understanding and optimizing the management of CARDS.